Governance and competitiveness in global value chains: A comparative study in the automobile and textile industries - Pla-Barber, José; Villar, Cristina (Economics and Business Review, 2019)
In this paper the configuration of the value chains in the automobile and thetextile industries building on a theoretical review of the value chain concept, its differenttypologies and governance models are analised. At the empirical level these chainsare classified according to the most relevant participating actors, their interrelations andtheir methods of upgrading their competitiveness. In both chains a firm-level analysisof their quantitative indicators for competitiveness was carried out.Regarding the automobile industry assemblers generate significant agglomerationeconomies by attracting international suppliers. The modular production system of thesector generates great flexibility for the manufacturer but it also represents importantopportunities for supplier companies aiming to improve their competitive position inthese chains. As for the textile industry, our paper shows the clear leadership of thelarge distribution chains which have radically changed the sector transforming it intoan industry driven by the buyers or distributors. Results indicate that the distributioncompanies are those that have the potential to generate greater added value when thesecompanies have created integrated structures at the end of the chain.